Articulation, divergences and engagements: history teachers in a virtual facebook community (Tempo e Argumento, 2020)
This article proposes to analyze the forms of interaction built between basic education teachers in a closed virtual Facebook community, named “Dynamic History Teaching”. In it, there are more than 24 thousand History professionals working in different stages of teaching, within public and private schools and from the most varied regions and contexts in Brazil. We argue that the community can be seen as an informal space of continuing  formation of historians working in brazilian basic education, indicating potentiality for the constitution of “communities of experiences” regarding historical knowledge. We chose methodologically to build an ethnography of school practice, choosing the axes of articulation, divergences and engagement, but in this case, having a digital platform as the locus. Firstly, we seek to comprehend the mechanisms that teachers use to build ways of mutual cooperation within this virtual community. Then, we aim to understand if the educators show theoretical and  political dissension, noticing in which terms those divergences manifest in the different posted dialogues. Demonstrating that the community works as a space where teachers share different methodological strategies, we seek to argue how these debates are situated between critical perspectives and a reinforcement of “technique by technique”.Keywords: History Teachers. History Teaching and Learning. Teachers Continuing Education. Virtual Community. Bell Hooks.